DUKUNGAN SOSIAL PASANGAN DAN WORK FAMILY CONFLICT PADA GURU HONORER WANITA - Frans; Rahmi, Tutiq; Febriani, Utari; Dita, Izmi Ayuning; Rahmi, Tuti (CV. Causalita Dynamic Solutions, 2023)
This research aims to determine the relationship between partner social support and work family conflict in female honorary teachers. The approach to this research is a quantitative approach using survey methods. Data were collected using a scale of partner social support and work family conflict and the data was processed using product moment correlation analysis. 84 female honorary teachers participated in this research. Based on the results of data analysis and the results of coirielation analysis with a coirielation value of around 0.585. The results of research hypothesis testing show that there is a relationship between partner social support and work family conflict in female elementary school honorary teachers.